Implementasi Pendidikan Karakter di Sekolah Katolik dalam Terang Dokumen Educating to Fraternal Humanism - Henderikus Dasrimin (Studia Philosophica et Theologica, 2023)
The teaching of biblical inspiration is one of the basic understandings of the Bible in the Catholic Church. Reading and using the Bible does not guarantee the correct understanding of biblical inspiration. Therefore, this article intends to examine the understanding of biblical inspiration by the Christians and the church's teaching in the documents Dei Verbum and The Inspiration and Truth of Sacred Scriptures. This study uses qualitative method with a field study and literature study. Through this study, an understanding was obtained that the Christians have not understood the teaching of biblical inspiration correctly based on the church’s teaching, where inspiration signifies the cooperation between God and humans in writing the Scriptures. Thus the church needs to make a pastoral service to explain the church's teaching about biblical inspiration correctly.